AP P L ICAT ION IN SAL E S T RANSAC T IONS WI TH ABC MINIMARKET VISUAL BASIC 6.0 - Candra Ari Yanto (Jurnal Manajemen Informatika, 2010)
Market is the place of purchase and sale transactions, one type of marketThere is a modernmini-business.Unlike traditionalmarket sales transactionsmanually, on salesminimarket items of household needs (daily needs) is done retail and self-servicemanner. To help process sales transactions in minimarket an application requires thesale, so business can minimarket going well and sales transactions become moreeffective, efficient and profitable.Therefore, the authors make writing with the title Application Transaction Sales at ABCMinimarketWith Visual Basic 6.0.